Institutional Reformulation in Music Royalty Management in Indonesia: A Comparative Study with Germany and France - Abdul Haris Nafis; Suherman Suherman; Iwan Erar Joesoef (Civiliza Publishing, 2026)
The normative management of song and/or music copyright royalties in Indonesia has been designed to adhere to a one-gate system through the National Collective Management Institute (LMKN), but in practice it is still colored by institutional fragmentation at the sectoral Collective Management Institution (LMK) layer, high operational cost cuts, and weak transparency in the Song and/or Music Information System (SILM). This research aims to analyze juridical problems and the implications of institutional fragmentation on the transparency of royalty management, as well as to formulate an ideal institutional reformulation model based on comparative studies with the Gesellschaft für musikalische Aufführungs- und mechanische Vervielfältigungsrechte (GEMA) in Germany and the Société des auteurs, compositeurs et éditeurs de musique (SACEM) in France. The research uses normative juridical methods with legislative, conceptual, and comparative approaches. The results of the study show that the root of the problem stems from the weakness of the substance of the regulation that legitimizes the multiplicity of LMKs, thereby triggering financial inefficiency, overlapping authority, and low distribution accountability. Comparative studies show that the success of GEMA and SACEM rests on institutional centralization, strict state supervision, and transparent audits. This study recommends an integrated one-stop institutional reconstruction accompanied by a revision of Government Regulation Number 56 of 2021 to ensure legal certainty and openness for creators, musicians, and copyright holders.